2021
DOI: 10.3390/su131810185
|View full text |Cite
|
Sign up to set email alerts
|

SMEs during the COVID-19 Pandemic Crisis. The Sources of Problems, the Effects of Changes, Applied Tools and Management Strategies—The Example of Poland

Abstract: Purpose: The aim of the theoretical deliberations and empirical research conducted is to determine the basic sources of problems in the SME sector of enterprises in Poland during the COVID-19 pandemic crisis, and to present how enterprises are responding to external changes and adapting to these changes. The consideration of four types of enterprise strategies in the context of a large scale and a strong influence of external conditions on their activities is the leitmotif of the undertaken research. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Becker et al [60] point out that one of the business characteristics with the greatest impact on the momentum of the crisis in companies is the reliance on physical proximity, which is inherent for hotel services. A study conducted in Poland, for example, showed that, among the companies that declared bankruptcy and restructuring in 2020, the most represented were those in the services sector, with the accommodation and catering sectors particularly affected, and with the increase in bankruptcies being as high as 186% [61]. The accommodation sector has been strongly affected by the crisis, whereby the "new normal" measures have resulted in hotels adapting in order to maintain their business [41].…”
Section: Business and Bankruptcy Crisis In The Travel And Tourism Ind...mentioning
confidence: 99%
“…Becker et al [60] point out that one of the business characteristics with the greatest impact on the momentum of the crisis in companies is the reliance on physical proximity, which is inherent for hotel services. A study conducted in Poland, for example, showed that, among the companies that declared bankruptcy and restructuring in 2020, the most represented were those in the services sector, with the accommodation and catering sectors particularly affected, and with the increase in bankruptcies being as high as 186% [61]. The accommodation sector has been strongly affected by the crisis, whereby the "new normal" measures have resulted in hotels adapting in order to maintain their business [41].…”
Section: Business and Bankruptcy Crisis In The Travel And Tourism Ind...mentioning
confidence: 99%
“…Only a few of those investigations have paid attention to the importance of searching for techniques to relieve such stress and reduce TI during the pandemic. Furthermore, we can observe that SMEs have been the worst affected sector during this particular pandemic situation, where a huge loss of jobs has been evident [ 22 , 23 , 24 , 25 ]. Therefore, there is a substantial gap regarding research investigations on the impact of COVID-19 related JS on TI, particularly within SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…This condition causes restrictions on the movement of people. Several challenges that result from the COVID-19 pandemic include declined demand, supply chain disruptions, furloughed employees, quarantine or exposure, closure of borders between cities/countries, payment delays, and market uncertainty [16]. [17] stated that the COVID-19 pandemic is a unique crisis that has a variety of effects on businesses, including supply (reduction in labor supply due to stayat-home workers, lack of resources, disruption of supply chains); demand (reduced demand due to loss of customers, precautions, cautious investors); uncertainty (inability to rely on future revenue streams, e.g., replacement of employees or equipment), and unavailability of funding.…”
Section: Resultsmentioning
confidence: 99%